Fossilization transforms vertebrate hard tissue proteins into N-heterocyclic polymers - Jasmina Wiemann (Nature Portfolio, 2018)
Recent studies have reported preservation of proteinaceous soft tissues within dinosaur bones. Here, Wiemann et al. combine analyses of fossil vertebrate tissues and experimentally matured modern samples to elucidate the mechanism of soft tissue preservation and the environments that favor it.